Structure and biochemical functions of four simian virus 40 truncated large-T antigens. - Chaudry, F (1982)
The structure of four abnormal T antigens which are present in different simian virus 40 (SV40)-transformed mouse cell lines was studied by tryptic peptide mapping, partial proteolysis fingerprinting, immunoprecipitation with monoclonal antibodies, and in vitro translation. The results obtained allowed us to deduce that these proteins, which have apparent molecular weights of 15,000, 22,000, 33,000 and 45,000, are truncated forms of large-T antigen extending to different amounts into the amino acid sequences unique to large-T. The proteins are all phosphorylated, probably at a site between amino acids 106 and 123. The mRNAs coding for the proteins probably contain the normal large-T splice but are shorter than the normal transcripts of the SV40 early region. The truncated large-Ts were tested for the ability to bind to double-stranded DNA-cellulose. This showed that the 33,000- and 45,000-molecular-weight polypeptides contained sequences sufficient for binding under the conditions used, whereas the 15,000- and 22,000-molecular-weight forms did not. Together with published data, this allows the tentative mapping of a region of SV40 large-T between amino acids 109 and 272 that is necessary and may be sufficient for the binding to double-stranded DNA-cellulose in vitro. None of the truncated large-T species formed a stable complex with the host cell protein referred to as nonviral T-antigen or p53, suggesting that the carboxy-terminal sequences of large-T are necessary for complex formation.